Market discipline and liquidity risk: Evidence from the interbank funds market - Miguel Sarmiento (Graduate Institute of International and Development Studies, 2016)
This paper identifies bank-specific-characteristics and market conditions that contribute to determine prices and demand for liquidity in the interbank market as wells as banks' access to this market. Results indicate that riskier banks pay higher prices and borrow less liquidity, concurrent with the existence of market discipline. More capitalized and liquid banks tend to pay less for their funds and to have greater access to the interbank market. We find that banks pay higher prices and hoard liquidity when liquidity positions across them are more imbalanced and during a monetary policy tightening. Besides, small banks are found to suffer more as their credit risk and liquidity risk increase. We show that lending relationships benefit banks in hedging liquidity risk. We also document that central bank liquidity increments are associated with a downward pressure on interbank funds' prices and augmented market activity. Overall, our results have implications for financial stability and for the transmission of the monetary policy as well.
Keywords: E43; E58; L14; G12; G21; 330; interbank markets; market discipline; liquidity risk; risk taking; monetary policy; financial stability